Management Readiness Factors for Enhancing the Competitiveness of Hostel Businesses for Tourism in Phra Nakhon Si Ayutthaya Province - Soithongphong, Thiyada; Rakliang, Naruechit; Chaiwinij, Wachiraya; Sittijuk, Pramote (Journal of Dhamma for Life, 2025)
This research aimed to: (1) examine the management readiness factors and the capabilities of hostel businesses in promoting tourism in Phra Nakhon Si Ayutthaya Province, and (2) investigate the relationship between these readiness factors and the capabilities of hostel businesses in supporting tourism within the province. The sample consisted of 340 hostel business owners and employees, determined using Taro Yamane’s formula with a 95% confidence level. Simple random sampling was employed, and data were collected through a questionnaire designed to explore factors influencing the development of hostel business capabilities in Phra Nakhon Si Ayutthaya. Data analysis was conducted using mean scores, standard deviations, and Pearson’s correlation coefficients. The findings revealed that hostel businesses in the province exhibited a high overall level of management readiness. The highest-rated factor was personnel readiness, while the lowest was performance evaluation and quality control. The overall capability of hostels in promoting tourism was also rated high, with the ability to adapt marketing strategies being the strongest, and risk management the weakest. A significant correlation was found between personnel readiness and business capability. Furthermore, efficient operational systems and the adoption of appropriate technologies were found to play a crucial role in enhancing service quality.